Effect of dexmedetomidine on characteristics of ultrasound-guided supraclavicular brachial plexus block with levobupivacaine-A prospective double-blind randomized controlled trial - Bhumireddy Suneel Reddy; Yogesh K Gaude; Shriram Vaidya; Gurudas K Kini; Lokvendra S Budania; M V Eeshwar (Wolters Kluwer Medknow Publications, 2021)
Background and Aims: Levobupivacaine, a less cardiotoxic s-isomer of bupivacaine, is proved to be similar to bupivacaine, hence, proposed as a safer alternative for nerve blocks. We aimed to evaluate the effect of perineural and intravenous dexmedetomidine on characteristics of ultrasound-guided supraclavicular brachial plexus block (BPB) performed with levobupivacaine. The aim of this study is to evaluate the effect of perineural and intravenous dexmedetomidine on characteristics of ultrasound-guided supraclavicular BPB performed with levobupivacaine. Material and Methods: A prospective, randomized double-blind control trial done on 120 patients undergoing elective upper limb surgical procedures under supraclavicular BPB. The enrolled patients were allocated to one of the three groups: Group L - 0.5% levobupivacaine +0.9% normal saline (NS) IV infusion; Group LDI - 0.5% levobupivacaine + dexmedetomidine (1 mcg/kg) in NS IV infusion; and Group LDP - 0.5% levobupivacaine +1 mcg/kg of dexmedetomidine perineural + NS IV infusion. The onset and duration of sensory and motor blockade were recorded in minutes. One-way ANOVA was used to observe any differences between the groups, and post hoc comparisons were conducted after Bonferroni correction for multiple comparisons. Results: The onset of sensory and motor blockade in Group LDP was significantly shorter than Group L and Group LDI. The duration of sensory blockade in Group LDP was significantly longer than Group LDI and Group L. The duration of motor blockade in Group LDP was prolonged compared to Group LDI and Group L. Conclusions: When dexmedetomidine is added as adjunct to levobupivacaine in supraclavicular BPB, onset of sensory and motor blockade is faster in perineural group, whereas duration of sensory and motor blockade and duration of analgesia are more prolonged when used perineurally than intravenously.